BEYOND NEOLIBERALISM, THE EMERGENCE OF LATIN AMERICA PINK TIDE (POST WASHINGTON CONSENSUS AND NEOSTRUCTURALISM) - Muhammad Dudi Hari Saputra (UIN ALAUDDIN MAKASSAR, 2019)
This paper aims to analyze the emergence of Latin America Pink Tide and others, especially in political-economic paradigm (liberalism, neoliberalism and post-neoliberalism). Firstly, this paper describes an international political economy development generally and theoretically. Secondly, it describes political economy conditions in Latin America. Thirdly, it analyzes neoliberalism context that affects the development process in Latin America countries. Fourthly, it analyzes neoliberal development model, which is adopted in the context of Latin America. Fifthly, author is trying to address alternatives of neoliberalism development model that was conceived and adopted by the countries in Latin America, associate with pink tide phenomenon that recently emerging up in most countries in Latin America. Keywords: Alternative model, Development, International Political Economy, Latin America, Liberalism, Neoliberalism, Post-neoliberalism and Pink Tide.